Influence of curing conditions on mechanical behaviour of glued joints of carbon fibre-reinforced polymer composite/concrete. (10th December 2019) - Lee, A.T.; Michel, M.; Ferrier, E.; Benmokrane, Brahim
Highlights: Carbon fiber reinforced polymer. Tensile strength. Glass transition temperature. Curing conditions. Bond on concrete. Abstract: Polymeric adhesives are widely used for the bonding of carbon fibre-reinforced polymers (FRPs) on a concrete structure. Structural reinforcement using FRPs is a very efficient strategy owing to the good mechanical characteristics of FRPs and the implementation methods, which are applied onsite and make it possible to reduce the work time. Efficiency is limited by FRP debonding and adhesive has a key issue to play in the strengthening. Working onsite assumes that the conditions for implementation are highly dependent on the climate. In this context, it should be noted that the resins used are cold-curing epoxy and that their mechanical and physical properties are temperature- and humidity-dependent. In this study, the impact of the application temperature on the behaviour of composite reinforcement is investigated. The objective is to analyse the mechanical and physical behaviour of epoxy polymers used for reinforcement by measuring the mechanical properties of composite adhesion on a concrete support via double-shear and pull-out tests, as well as the glass transition temperatures Tg. The Tg measurements are performed using differential scanning calorimetry and thermomechanical analysis. Double-shear tests are performed to establish the local composite-to-concrete shear laws for adhesive joints according to the nature of the polymers and the curing conditions. The test results allow for determination of the bonding length (Le) and its dependence on the curing conditions. The physical measurements of Tg support the study by elucidating the influence of the curing conditions on these properties.